Pengembangan E-Modul Berbasis PBL dengan Media Wepik Terhadap Peningkatan Kemampuan Literasi Sains dan Numerasi Siswa MA - Karmila, Mila; Abidin, Zaenal; Sulistyono, Sulistyono (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the feasibility, applicability, effectiveness and student response to PBL-based e-modules towards improving scientific literacy and numeracy skills of MA Al-Ishlah Majalengka students. This research was conducted from April to May 2023. The population in this study were MA students in class X MIPA, the sample consisted of 25 students in class X MIPA 1 as the experimental class and X MIPA 2 consisted of 25 students as the control class. The research design used in this study is a research development approach (Research and Development) with data collection techniques using tests, observations, and questionnaires. Data were analyzed using SPSS 2.0 software. The results showed 1) PBL-based E-Modules with Wepik media were very suitable for use as teaching materials in learning with an average score of 93.33% from material experts, 92.50% from linguists, 97.11% from media experts; The implementation of E-Module learning with wepik media gets an average percentage score of 86.66% in the good category; 3) The effectiveness of PBL-based E-Modules with Wepik media uses the Effect Size formula for scientific literacy skills with Cohen's scores of 3.70 and 2.18 for numeracy literacy. The Effect Size category of scientific literacy and numeracy skills is large, which means it is effectively used as teaching material; 4) Student responses to learning using the E-Module with Wepik media are included in the positive and very good criteria. The conclusions from this study are: 1) The feasibility of the E-Module based on expert validation is stated to be very suitable for use as teaching material; 2) The implementation of learning using E-Modules with Wepik media is very good in improving students' scientific literacy and numeracy skills; 3) There is a significant difference in the increase in scientific literacy and numeracy skills between the experiment and the control; 4) Students give a positive response to E-Module learning with wepik media on environmental change material.